Crosstalk between ubiquitin ligases and ncRNAs drives cardiovascular disease progression - You, Jia-Rui; Wen, Zeng-Jin; Tian, Jia-Wei; Lv, Xiao-Bing; Li, Rong; Li, Shu-Ping; Xin, Hui; Li, Pei-Feng; Zhang, Yin-Feng; Zhang, Rui (Frontiers in Immunology, 2024)
Cardiovascular diseases (CVDs) are multifactorial chronic diseases and have the highest rates of morbidity and mortality worldwide. The ubiquitin-proteasome system (UPS) plays a crucial role in posttranslational modification and quality control of proteins, maintaining intracellular homeostasis via degradation of misfolded, shortlived, or nonfunctional regulatory proteins. Noncoding RNAs (ncRNAs, such as microRNAs, long noncoding RNAs, circular RNAs and small interfering RNAs) serve as epigenetic factors and directly or indirectly participate in various physiological and pathological processes. NcRNAs that regulate ubiquitination or are regulated by the UPS are involved in the execution of target protein stability. The cross-linked relationship between the UPS, ncRNAs and CVDs has drawn researchers' attention.Herein, we provide an update on recent developments and perspectives on how the crosstalk of the UPS and ncRNAs affects the pathological mechanisms of CVDs, particularly myocardial ischemia/reperfusion injury, myocardial infarction, cardiomyopathy, heart failure, atherosclerosis, hypertension, and ischemic stroke. In addition, we further envision that RNA interference or ncRNA mimics or inhibitors targeting the UPS can potentially be used as therapeutic tools and strategies.